The influence of the work palce on the information seeking behiour and information utilization of Agricultural engineers (2001)
Factors which influence the information seeking behaviour and information utilization of different professional groups have been the subject of much investigation. This study examined whether or not there were significant differences in the information seeking behaviour and information utilization of Nigeiran agricultureal engineers employment in four different work enviroments, viz tertiary institutions, public sector/ministry, private sector, and research institutes. A stratified random sample of 261 out of the 671 registered agricultural engineers in Nigeria eas selected; proportional allocation was used to obtain sample size for each statum. Questionnaires were administered to all groups. Result showed significantt differences in the information seeking behaviour of the respondents in respect of thier palces of work (F-20.226, df=3,257,p<0.05). Additional results indicated no significant differences in information utilization of respondents based on thier work places. Recommendations pertient to the work situation of agricultural engineers in Nigeria were suggested.